Changes in the hypothalamus in relation to testicular cells during growth, maturation and spawning phases in the brackishwater teleost Liza parsia (Hamilton, 1822) - Bose, S.; Chakrabarti, P. (Indian Journal of Fisheries, 2018)
In the present investigation, different cell types in the hypothalamus of the goldspot mullet Liza parsia (Hamilton, 1822) were characterised on the basis of their arrangement, distribution and tinctorial properties. The hypothalamic neurosecretory system of L. parsia is made up of two nuclei rich areas viz., nucleus pre-opticus (NPO), nucleus lateralis tuberis (NLT) and their axonal pathways. The NPO is vertically organised and the cells are arranged in an oblique plane on either side of the third ventricle. The larger cells viz., pars magnocellularis (PMC) are dorsally placed whereas smaller cells, pars parvocellularis (PPC) are placed ventrally to the third ventricle. Fine thread like axons stained with chrome-alum-haematoxylin-phloxine (CAHP) extend from preoptic cells to the close proximity of blood capillaries. Cells of the NLT are paired and situated above the pituitary gland. The cells of NPO and NLT exhibited both quantitative and qualitative variations during different periods of the testicular maturation. During growth and maturation periods, cells of PMC and NLT were characterised by intense staining and dense homogeneous granules along with deposition of neurosecretory materials. During spawning period, slight decrease in staining affinity of the cells of PMC and NLT were recorded. Changes in the testes of L. parsia have been described according to variations in gonadosomatic index (GSI) values and frequency percentages of different male germ cells during growth, maturation and spawning phases.